Influential Factors Affecting Students’ Achievement in Higher Education Institution System - Widiarini Widiarini; Achmad Supriyanto; Asep Sunandar (Journal of Development Research, 2023)
Instead of focusing on institution ranking, HEI should consider the students’ achievements because new students’ admission regulation allotted 20% of students registered by using achievement evaluation. In addition, every HEI must report student management, including students’ achievements through SIMKATMAWA. Bear in mind, the importance of student management and students’ achievement, the aim of this study is to investigate the relationship of factors affecting students’ achievement such as new students’ state university admission, students’ achievement motivation, students’ services, reward system, and students’ achievement. The researcher used a non-experimental quantitative approach i.e., correlational research. The sample of this study was 78 students of Brawijaya University (UB) who have high achievements. Structural equation modeling (SEM) was chosen as an analytical technique. This study showed a positive relationship between new students’ admission, students’ service, reward system, and students’ achievement. Those variables had a direct relationship. In addition, there was no significant positive relationship between new students’ admission for students’ achievement motivation, as well as students’ service for students’ achievement motivation. In sum, this study showed that UB had a good students management system, so that the students can get achievements.